2009
DOI: 10.1371/journal.pone.0007599
|View full text |Cite
|
Sign up to set email alerts
|

Poor Prognosis with In Vitro Fertilization in Indian Women Compared to Caucasian Women Despite Similar Embryo Quality

Abstract: BackgroundDisease prevalence and response to medical therapy may differ among patients of diverse ethnicities. Poor outcomes with in vitro fertilization (IVF) treatment have been previously shown in Indian women compared to Caucasian women, and some evidence suggests that poor embryo quality may be a cause for the discrepancy. In our center, only patients with the highest quality cleavage stage embryos are considered eligible for extending embryo culture to the blastocyst stage. We compared live birth rates (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
(21 reference statements)
2
27
0
Order By: Relevance
“…White women may be more likely to have PCOS, endometriosis, and/or other ovulation disorders compared with black or Hispanic women, and there is conflicting evidence on whether PCOS is more common in Asians than whites undergoing IVF (19,21,24,37,(49)(50)(51)(52). Though unlikely to fully explain disparities, ethnic differences in the prevalence and metabolic/reproductive consequences of PCOS have been previously identified (14).…”
Section: Infertility Diagnosismentioning
confidence: 99%
“…White women may be more likely to have PCOS, endometriosis, and/or other ovulation disorders compared with black or Hispanic women, and there is conflicting evidence on whether PCOS is more common in Asians than whites undergoing IVF (19,21,24,37,(49)(50)(51)(52). Though unlikely to fully explain disparities, ethnic differences in the prevalence and metabolic/reproductive consequences of PCOS have been previously identified (14).…”
Section: Infertility Diagnosismentioning
confidence: 99%
“…In two separate studies, again in the USA, lower live birth rates were reported in South Asian Indian women compared with white women, despite their younger age and lower basal follicle stimulating hormone (FSH) levels 10,11. Less than a handful of studies reported no differences in assisted reproductive technology (ART) outcome between Hispanic and white women,12 or between African-American and white women 13,14.…”
Section: Introductionmentioning
confidence: 99%
“…There are little data on genital tuberculosis in the United States, as it is relatively uncommon except in immigrant populations. Shahine et al [ 15 ] and Sharara coworkers [ 16 ] showed no difference in the incidence of tubal factor between the South Asians and Caucasians in their studies.…”
Section: Genital Tuberculosis/tubal Factormentioning
confidence: 88%
“…In contrast to the study by Palep-Singh et al, the two groups had similar number of oocytes retrieved, fertilization rates, and mean number of blastocysts. Despite a younger average age, similar response to ovarian stimulation, and comparable embryo quality, the Indian patients had signifi cantly lower clinical pregnancy rates (36 % vs. 52 %) and LBR (24 % vs. 41 %) than the Caucasian patients [ 15 ]. Sharara et al performed a similar study in Virginia, comparing South Asian women to Caucasian women undergoing fresh blastocyst transfer (see Table 8.2 ).…”
Section: Art Outcomes Among Women Of South Asian Ethnicitymentioning
confidence: 99%